Early vocational rehabilitation for people with spinal cord injury: a research protocol using realist synthesis and interviews to understand how and why it works. Issue 5 (3rd May 2021) - Dunn, Jennifer; Martin, Rachelle A; Hackney, Jonathan J; Nunnerley, Joanne L; Snell, Deborah; Bourke, John A; Hall, Andrew; Derrett, Sarah
Abstract : Introduction: Return to work after spinal cord injury (SCI) is linked to well-being and better physical and mental health outcomes. In New Zealand, work rates after SCI are lower than the general population. Vocational rehabilitation is one method of supporting return to work. Although the best model has not been determined, there is evidence supporting early intervention. However, most vocational rehabilitation research focuses on return to work outcomes without considering why vocational rehabilitation works, for whom and under what circumstances. Given this knowledge gap, we detail a realist synthesis protocol aiming to explain how contextual factors trigger relevant mechanisms to facilitate return to work after SCI. Methods and analysis: This study will use a realist synthesis approach, following Realist And MEta-narrative Evidence Synthesis: Evolving Standards (RAMESES) guidelines. First, we will undertake a realist review of existing published and grey literature. Second, to assist with theoretical conceptualisation, we will interview people with SCI who have received vocational rehabilitation. Finally, we will survey people with SCI who received early vocational rehabilitation for theoretical testing and refinement. Ethics and dissemination: University of Otago Ethics Committee (Reference H19/170) has been obtained. A knowledge translation event will address issues relevant to wider implementation of the intervention and study findings. Findings will be also be disseminated through peer reviewed journals, conference presentations and formal reports.